Pemanfaatan Media Cyber Konseling dalam Meningkatkan Mutu Layanan Bimbingan Konseling di MAN 3 Langkat - Harahap, Ade Chita Putri; Hasibuan, Ahmad Anas; Lestari, Ayu Ari; Asmaida, Asmaida; Indriany, Dina; Berasa, Muslimah; Barira, Sopia; Heriawan, Mhd Yogi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Cyber counseling media can be an effective tool in improving the quality of counseling services at MAN 3 Langkat School. This media can help students who are difficult to reach directly to get counseling, provide easy access, improve the effectiveness and efficiency of services, expand the reach of services, and increase security. However, in using cyber counseling media, it is necessary to pay attention to several things such as student data privacy and security, technology security, and applicable regulations. The school must ensure that cyber counseling services are carried out in compliance with professional ethics and applicable laws in Indonesia. In this case, cyber counseling media can help improve the quality of counseling services at MAN 3 Langkat School.